Consecutive Extratropical Cyclones Daniel, Elsa and Fabien, and Their Impact on the Hydrological Cycle of Mainland Portugal - Milica Stojanovic; Ana Gonçalves; Rogert Sorí; Marta Vázquez; Alexandre M. Ramos; Raquel Nieto; Luis Gimeno; Margarida L. R. Liberato (Water, 2021)
The extratropical cyclones that originate in the North Atlantic and propagate towards Europe are one of the major natural hazards in mid-latitudes. In December 2019, three consecutive extratropical cyclones named Daniel, Elsa, and Fabien affected Portugal. In this study, the synoptic and upper-level dynamic conditions associated with these systems during their impact in mainland Portugal are evaluated. The persistent intense zonal flow that crossed the entire Atlantic revealed by the integrated vapor transport and the vertically integrated moisture flux favored these hydro-meteorological systems. The patterns of mean sea level pressure, geopotential, potential vorticity, total column water, and convective available potential energy were used to characterize the influence of every system over mainland Portugal. A cluster analysis of monthly precipitation permitted the classification of the country into four main regions named the Northwest, Centre West, Northeast and Centre East, and South region on which the analysis was focused. The three storms affected every region on consecutive days by the middle of December, producing extreme precipitation events and significant effects on the accumulated rainfall and runoff, particularly in the Northwest, Centre West, Northeast and Centre East regions. As consequence, multiple incidences of damage were reported along mainland Portugal. However, an assessment of the Standardized Precipitation Index (SPI) and the Standardized Precipitation–Evapotranspiration Index (SPEI) on time scales of 1, 3, 6, and 12 months revealed a positive impact of rainfall increase on the attenuation of short and long term accumulated drought conditions, particularly in the center and north regions.